2003
DOI: 10.1021/bi0346704
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis of Benzo[a]pyrene Diol Epoxide in Yeast:  Requirement for DNA Polymerase ζ and Involvement of DNA Polymerase η

Abstract: Benzo[a]pyrene is a potent environmental carcinogen, which can be metabolized in cells to the DNA damaging agent anti-benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide (anti-BPDE). We hypothesize that mutations induced by BPDE DNA adducts are mainly generated through an error-prone translesion synthesis that requires a specialized DNA polymerase (Pol). Using an in vivo mutagenesis assay in the yeast model system, we have examined the potential roles of Pol(zeta) and Pol(eta) in (+/-)-anti-BPDE-induced mutagenesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 33 publications
3
46
0
1
Order By: Relevance
“…One study found that (±)-anti-BPDE also caused G>T transversions in the same yeast assay that we use. However, another study found a preference for G>C transversions in a yeast mutagenesis assay with (±)-anti-BPDE (40). The preference for G to C over G to T transversions may be governed by the trans-lesional by pass polymerase Polζ which has been shown to preferentially incorporate G opposite an (+)-anti-BPDE-N 2 -dGuo adduct in yeast strains proficient in mutagenesis (40).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that (±)-anti-BPDE also caused G>T transversions in the same yeast assay that we use. However, another study found a preference for G>C transversions in a yeast mutagenesis assay with (±)-anti-BPDE (40). The preference for G to C over G to T transversions may be governed by the trans-lesional by pass polymerase Polζ which has been shown to preferentially incorporate G opposite an (+)-anti-BPDE-N 2 -dGuo adduct in yeast strains proficient in mutagenesis (40).…”
Section: Discussionmentioning
confidence: 99%
“…8588 Synthesis opposite the bulky N 2 -dG adducts is slow, 67 although pol η may play a role in the mutagenic bypass of N 2 -BP-dG. 68,89,90 These studies do not provide any mechanistic rationale for the ability of pol η to insert dTTP and dATP opposite O 2 -alkyl-dT. Our in vitro kinetic data do agree with the mammalian cell culture studies in which pol η is crucial to the bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of G>T transversions seems to be concentration-dependant [31]. Interestingly, using a yeast assay with various strains deficient in nucleotide excision repair, it was demonstrated that DNA polymerases η and ζ were required in combination for the translesion repair across BPDE adducts, leading to G>T transversions [35]. Pol ζ alone was also able to generate large deletions in this assay.…”
Section: Discussionmentioning
confidence: 99%